2011
DOI: 10.2215/cjn.06140710
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Gelatinase-Associated Lipocalin in the Diagnosis of Type 1 Cardio-Renal Syndrome in the General Ward

Abstract: SummaryBackground and objectives The early identification of acute heart failure (HF) patients with type 1 cardiorenal syndrome should be the first step for developing prevention and treatment strategies for these patients. This study aimed to assess the performance of neutrophil gelatinase-associated lipocalin (NGAL) and cystatin C in the early detection of type 1 cardio-renal syndrome in patients with acute HF.Design, setting, participants, & measurements One-hundred nineteen patients admitted with acute HF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 32 publications
(34 reference statements)
2
63
1
4
Order By: Relevance
“…[9][10][11][12] To date, only a few small clinical studies have tested the utility of these biomarkers, mostly NGAL, in predicting acute CRS and have yielded only modest performance in general. [13][14][15][16][17][18][19] In addition, there is a particular lack of predictors for longer-term prognosis in patients with acute CRS. In each of these circumstances, the early detection of patients at high risk of developing AKI, before a detectable change in serum creatinine, would afford clinicians a critical time window to halt or reverse the ongoing renal injury.…”
mentioning
confidence: 99%
“…[9][10][11][12] To date, only a few small clinical studies have tested the utility of these biomarkers, mostly NGAL, in predicting acute CRS and have yielded only modest performance in general. [13][14][15][16][17][18][19] In addition, there is a particular lack of predictors for longer-term prognosis in patients with acute CRS. In each of these circumstances, the early detection of patients at high risk of developing AKI, before a detectable change in serum creatinine, would afford clinicians a critical time window to halt or reverse the ongoing renal injury.…”
mentioning
confidence: 99%
“…specificity of 86.7% when the cut-off was 170 ng/ml. 15 However, the number of patients with AKI (n=14) in the study was low. Two investigations by Tang et al explored the association between urinary NGAL and different aspects of renal dysfunction.…”
Section: Resultsmentioning
confidence: 92%
“…[11][12][13][14] Although prior research has revealed that NGAL, KIM-1, and Cys-C predict AKI in patients with ADHF separately, no study has examined whether combining markers of the 2 categories could improve diagnostic accuracy. [15][16][17][18][19] Thus, the present study investigated this hypothesis, compared the efficacy and accuracy of these markers, and explored the combined usage.…”
Section: Discussionmentioning
confidence: 99%
“…Only the admission NGAL measurement in acute decompensated HF was important to foresee AKI. 24 Hospitalized acute decompensated HF patients might have high admission serum NGAL levels despite normal admission creatinine values. 22 Serum and urine NGAL levels were found to be important to foresee disease progression in chronic kidney disease patients.…”
Section: Discussionmentioning
confidence: 99%